NCOG-05. MANAGEMENT OF BRAIN METASTASIS IN TRIPLE NEGATIVE BREAST CANCER. (9th November 2020) - Medikonda, Ravi; Srivastava, Siddhartha; Kim, Timothy; Xia, Yuanxuan; Patel, Mira; Jackson, Christopher; Theodros, Debebe; Kim, Jennifer; Kleinberg, Lawrence; Redmond, Kristin; Weingart, Jon; Mukherjee, Debraj; et al.
Abstract: Brain metastasis is common in patients with breast cancer, and those with triple negative status have an even higher risk. Stereotactic radiosurgery (SRS) is preferred to whole brain radiation therapy (WBRT) in most patients. However, triple negative status is currently not considered when determining optimal radiation therapy. Given the aggressive nature of triple negative breast cancer, we evaluated a role for WBRT for all patients in this cohort. We conducted a single-institution retrospective cohort study to determine whether triple negative patients with brain metastases have a higher burden of intracranial disease and whether type of initial radiation therapy affects overall survival for this cohort of patients. 85 patients met the inclusion criteria for this study. 25% of patients had triple negative breast cancer, of which 91% received SRS and 53% of patients received WBRT. The average number of new brain metastases from time of initial brain imaging to radiation therapy was 0.67 (St.Dev:1.1) in the non-triple negative status patients and 2.6 (St. Dev:3.7) in the triple negative status patients (p=0.001). Using a cox proportional hazards model, it was found that whole brain radiotherapy does not significantly affect overall survival in patients with triple negative breast cancer (p = 0.96). Our findings highlight the highly aggressive intracranial nature of triple negative breast cancer. Indeed, the rate of increase in brain metastases is significantly higher for triple negative patients compared to non-triple negative patients. As a result, we evaluated whether triple negative patients would benefit from whole brain radiation regardless of findings on initial brain imaging. Despite 53% of patients receiving WBRT, our investigation found that there is no additional benefit to WBRT in triple negative breast cancer patients. These results suggest a need to re-evaluate the role of WBRT in the management of triple negative breast cancer.